2007
DOI: 10.1016/j.joep.2005.12.001
|View full text |Cite
|
Sign up to set email alerts
|

Adding exchange to charity: A reference price explanation

Abstract: Charities often request donations while offering of a near-worthless token, like a key chain, in exchange. Little research has examined whether such 'exchange' requests are met with higher compliance rates than merely asking people to donate. Our studies suggest that in mere donation settings people may have difficulties to estimate a socially acceptable donation amount and therefore prefer opportunities that provide them with an anchor price. The value of a material good in a donation setting can play this an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 34 publications
(7 citation statements)
references
References 33 publications
(43 reference statements)
0
7
0
Order By: Relevance
“…The higher is consumers' perception of the donation, the more likely it is that decrease in direct donations will be under-compensated by indirect donations, leading to a decrease of overall funds raised by the NPO. This crowding out of donation is likely given that, most of the time, indirect donations are relatively small compared to direct donations (Briers et al, 2007).…”
Section: The Impact On the Global Amount Of Donationsmentioning
confidence: 99%
See 2 more Smart Citations
“…The higher is consumers' perception of the donation, the more likely it is that decrease in direct donations will be under-compensated by indirect donations, leading to a decrease of overall funds raised by the NPO. This crowding out of donation is likely given that, most of the time, indirect donations are relatively small compared to direct donations (Briers et al, 2007).…”
Section: The Impact On the Global Amount Of Donationsmentioning
confidence: 99%
“…Therefore, consumers may prefer opportunities that provide them with an anchor price (Fraser et al, 1988). Briers et al (2007) argues that a low-priced exchange product may signal a donation price that is lower than the perceived donation price in mere donation settings and may legitimize small contributions. This strategy renders most excuses for noncompliance (e.g., "We can't afford to help.")…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although a substantial body of research has examined the effects of product incentives on charitable giving (Briers, Pandelaere, & Warlop, 2007;Chao, 2017;Holmes, Miller, & Lerner, 2002;Newman & Shen, 2012;Simpson, Irwin, & Lawrence, 2006), to date, the majority of the research in this area has treated "donations with a gift" and "charitable purchases" as relatively interchangeable forms of product-based incentives. That said, a recent paper by Zlatev and Miller (2016) (hereafter, Z&M) directly compared these two types of offers and found that "charitable purchases" appear to encourage more giving than analogous "donations with a gift."…”
Section: Introductionmentioning
confidence: 99%
“…Nonprofit research showed that diverse "price" strategies help increase the funds collected. Some nonprofits frame the donation as a commercial exchange, i.e., they offer a small material present in exchange, such as donation ribbons or postcards (Briers, Pandelaere and Warlop, 2006). In such a situation, the social norm of reciprocity applies and people want to return the gift by making a fair donation.…”
Section: Pricementioning
confidence: 99%